DEVELOPMENT OF PJBL AND DEEP LEARNING TO IMPROVE STUDENT CREATIVITY IN PANCASILA INTEGRATED ARTS EDUCATION - Yuni Karsih Asmi; Sutrisna Wibawa; Insanul Qisti Barriyah; Ana Fitrotun Nisa; Heri Maria Zulfiati (SOSIOEDUKASI, 2025)
The development of the PjBL and Deep Learning models in Pancasila Education integrated with Arts and Culture can enable students to explore in designing projects accurately. This study aims to describe the development of the PjBL and Deep Learning models in Pancasila Education integrated with Arts and Culture. This research model uses the 4D model of development research (R & D) (define, design, develop, and disseminate). The development was carried out on developing teaching modules, the reference devices include teaching modules (learning plans), assessment instruments, student creativity observation sheets, student response questionnaires to learning activities, teacher response questionnaires to teaching modules. Data were collected using observation and questionnaire techniques. The research instruments used were questionnaires and observation sheets. The collected data were analyzed quantitatively to determine the average score, by categorizing based on the evaluation table referred to by the criteria, then analyzed qualitatively. This study found that: (1) the product was declared feasible after going through one revision with the addition of several components in each section from content experts, language, media, and practitioners and (2) the product was declared practical because it met the aspects of self-instruction, self-contained, stand alone, adaptive, and user friendly. Therefore, it is concluded that the Project Based Learning model with the Deep Learning approach on the material of applying Pancasila values in everyday life is feasible and practical to use in learning Pancasila Education integrated with Arts and Culture.